Accuracy Limits for the Thickness Measurement of the Hip Joint Cartilage in 3-D MR Images: Simulation and Validation - Cheng, Yuanzhi; Guo, Changyong; Wang, Yadong; Bai, Jing; Tamura, Shinichi (IEEE transactions on biomedical engineering, 2013)
This paper describes a theoretical simulation method for ascertaining the inherent limits on the accuracy of thickness measurement of hip joint cartilage in 3-D MR images. This method can specify where and how thickness can be measured with sufficient accuracy under the certain MR imaging conditions. In the numerical simulation, we present a mathematical model for two adjacent sheet structures separated by a small distance, which simulated the femoral and acetabular cartilage and the joint space width in the hip joint; moreover, we perform the numerical simulation of MR imaging and postprocessing for thickness measurement. We especially focused on the effects of voxel anisotropy in MR imaging with variable orientation of cartilage surface and different joint space width. Also, thickness measurement is performed in MR imaging with isotropic voxel. The results from MR data with isotropic voxels show that accurate measurement of cartilage thickness at location of measured values of the hip joint space width and the cartilage thickness being two times as large as the voxel size or above should be possible. The simulation method is validated by comparison with the actual results obtained from the experiments using three phantoms, five normal cadaver hip specimens, and nine patients with osteoarthritis.